Identification of Types of Coloring Agents and Artificial Sweeteners in Snacks at State Elementary School 1 Ilotidea, Tilango District, Gorontalo Regency, Gorontalo Province - andi meka (Diagnosa, 2025)
School snacks are one of the issues that require special attention from parents, educators, and school administrators, considering the health impacts that can arise from unsafe food additives. This study aims to identify the types of coloring agents and artificial sweeteners contained in snacks sold at State Elementary School 1 Ilotidea, Tilango District, Gorontalo Regency, Gorontalo Province. Coloring agents and artificial sweeteners, such as Rhodamine B and Saccharin, are commonly used in snack products to enhance attractiveness and flavor, despite both being potentially harmful to health if consumed in excess. This research uses laboratory analysis methods on snack samples taken from the school canteen and nearby vendors. The results show that most of the snacks contain synthetic coloring agents like Rhodamine B and artificial sweeteners like Saccharin and Cyclamate, which can cause negative health effects, including digestive problems and vision impairment. These findings indicate the need for stricter supervision of food additives in school snacks to protect children's health. This study is expected to serve as a basis for raising awareness and preventive actions related to food safety in school environments.